The Aggregator Role in V2G Assessing central aspects of the aggregator role in a Swedish V2G network - Bonnier Eklund, Elise; Lillieroth Gan, Lukas; Persson, Andreas; Johnson Swegmark, Wilhelm; Nihlstrand, Alexander; Thorslund, Anton (My University, 2023)
The electrification of society and increasing use of unpredictable renewable energy sources present significant challenges to the electrical grids. To assist in the transition towards a more renewable society, innovative technologies such as vehicle-to-grid can help flatten the energy demand curve and support the grid. Vehicle-to-grid can leverage the battery in electric vehicles to store electricity that can be used to power the grid when necessary. Although the technology exists, the economic landscape is relatively unexplored and needs to be understood in order to diffuse the technology. This thesis aims to identify the central aspects and structures required for the aggregator role in a Swedish vehicle-to-grid network and explore how an electric vehicle manufacturer could pursue this role. The area has been analyzed through interviews and a survey. The interviews explored different actors’ perception of the subject using a semi-structured interview method, whilst the survey complemented this by focusing on the views of electric vehicle users. The findings suggest that current actors have different competencies but only in their respective operations. To adopt an aggregator role, one must have a broader knowledge of the electricity system, aggregation, and customers. Collaboration and communication between electric vehicle users, aggregators, and grid operators will be essential for the network to operate efficiently. Preferences for compensation, ease of use, state of charge control, and transparency should be taken into consideration by aggregators in developing a compelling value proposition to acquire customers. Once analyzed, the results are placed in the context of realworld operations to provide a foundation for OEMs that wish to adopt an aggregator role in a V2G setting.
Keywords: V2G; vehicle-to-grid; electricity market; aggregator; aggregation; car manufacturer